2015
DOI: 10.3897/bdj.3.e4162
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary inventory of the catfishes of the lower Rio Nhamundá, Brazil (Ostariophysi, Siluriformes)

Abstract: The Rio Nhamundá is a poorly-known clearwater river draining the southern Guiana Shield of Brazil. In this study we report the findings of a preliminary ichthyological survey, focusing on catfishes (Siluriformes). We identify a total of 36 species (31 genera, seven families) from the Nhamundá, including 11 species already recorded from the river. Overall, our survey results show that even rapid surveys can provide important information on Amazon fish biodiversity, suggesting potential new species, providing ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 1,340 publications
(4 citation statements)
references
References 61 publications
(76 reference statements)
0
2
0
2
Order By: Relevance
“…The ichthyofauna of the Rio Nhamundá is poorly known, with Collins et al . () as the only available inventory from the lower Rio Nhamundá. In that study, 36 catfish species were reported for the basin, most of which are widespread in the lowland Amazon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ichthyofauna of the Rio Nhamundá is poorly known, with Collins et al . () as the only available inventory from the lower Rio Nhamundá. In that study, 36 catfish species were reported for the basin, most of which are widespread in the lowland Amazon.…”
Section: Discussionmentioning
confidence: 99%
“…The stretch has clear water and drains lowland Amazon rainforest nearly 40 m above sea level within the Floresta Estadual de Faro (Ávila-Pires et al, 2010;521 Freitas et al, 2017). The ichthyofauna of the Rio Nhamundá is poorly known, with Collins et al (2015) as the only available inventory from the lower Rio Nhamundá. In that study, 36 catfish species were reported for the basin, most of which are widespread in the lowland Amazon.…”
Section: Discussionmentioning
confidence: 99%
“…O rio localiza-se entre os rios Uatumã-Jatapú e Trombetas, e compreende a divisa administrativa entre os estados do Amazonas e do Pará (Carvalho de Lima e Araújo-Lima, 2004) (Figura 1.). É um dos principais rios da região Amazônica, no entanto, pouco conhecido, sendo um importante meio de transporte e fonte de subsistência para as comunidades ribeirinhas que vivem às suas margens (Collins et al 2015).…”
Section: Rio Nhamundáunclassified
“…A ictiofauna dos rios do sul do Escudo das Guianas é pouco conhecida em comparação com os rios do norte do Brasil (Lujan e Armbruster, 2011;Collins et al 2015), e até o presente poucos estudos científicos foram feitos nessa área, com exceção do rio Trombetas, que tem sido extensivamente pesquisado ao longo de vários anos (Ferreira, 1993;Campos, 2018;Garcia-Ayala e Benine, 2020).…”
Section: Rio Nhamundáunclassified